Mechanochemical Applications of Reactive Extrusion from Organic Synthesis to Catalytic and Active Materials - Emanuela Calcio Gaudino; Giorgio Grillo; Maela Manzoli; Silvia Tabasso; Simone Maccagnan; Giancarlo Cravotto (Molecules, 2022)
In the past, the use of mechanochemical methods in organic synthesis was reported as somewhat of a curiosity. However, perceptions have changed over the last two decades, and this technology is now being appreciated as a greener and more efficient synthetic method. The qualified “offer” of ball mills that make use of different set-ups, materials, and dimensions has allowed this technology to mature. Nevertheless, the intrinsic batch nature of mechanochemical methods hinders industrial scale-ups. New studies have found, in reactive extrusion, a powerful technique with which to activate chemical reactions with mechanical forces in a continuous flow. This new environmentally friendly mechanochemical synthetic method may be able to miniaturize production plants with outstanding process intensifications by removing organic solvents and working in a flow mode. Compared to conventional processes, reactive extrusions display high simplicity, safety, and cleanliness, which can be exploited in a variety of applications. This paper presents perspective examples in the better-known areas of reactive extrusions, including oxidation reactions, polymer processing, and biomass conversion. This work should stimulate further developments, as it highlights the versatility of reactive extrusion and the huge potential of solid-phase flow chemistry.